Directly embroidered microtubes for fluid transport in wearable applications. Issue 9 (5th April 2017) - Rahimi, Rahim; Yu, Wuyang; Ochoa, Manuel; Ziaie, Babak
Abstract : We demonstrate a facile approach for integrating highly flexible and stretchable microfluidics into textile-based substrates by directly embroidering surface-functionalized micro-tubing. Abstract : We demonstrate, for the first time, a facile and low-cost approach for integrating highly flexible and stretchable microfluidic channels into textile-based substrates. The integration of the microfluidics is accomplished by means of directly embroidering surface-functionalized micro-tubing in a zigzag/meander pattern and subsequently coating it with an elastomer for irreversible bonding. We show the utility of the embroidered micro-tubing by developing robust and stretchable drug-delivery and electronic devices. Controlled drug-delivery platforms with sustained release are achieved through selected laser ablated openings. We further demonstrate a wearable wireless resonant displacement sensor capable of detecting strains ranging from 0 to 60% with an average sensitivity of 45 kHz per % strain by filling the embroidered tubing with a liquid metal alloy, creating stretchable conductive microfluidics with <0.4 Ω resistance variations at their maximum stretchability (100%). The interconnects can withstand 1500 repeated stretch-and-release cycles at 30% strain with a less than 0.1 Ω change in resistance.